THE GLOBALIZATION AND CHILE - Tsvetkov, Tsvetomir; Ivanova, Lyubok (Revista Inclusiones, 2020)
The article examines the impact of the globalization on the economy of the Republic of Chile. The impact of the globalization on the dynamics of the Gross Domestic Product is considered in three aspects, namely economic, political and social. The study aims to analyze this impact by applying the generalized method of moments (GMM). The main empirical argument is that the globalization has a moderately beneficial effect on the economy of the Republic of Chile.